Survivors of Intimate Partner Violence as Advocates for Social Change - Christine E. Murray; Kelly King; Allison Crowe; Paulina Flasch (Journal for Social Action in Counseling and Psychology, 2015)
Intimate partner violence is a major public health issue that presents numerous potential challenges and negative consequences for survivors. The external barriers and systemic oppression that contribute to these challenges and consequences are potentially relevant factors for counselors to address in social justice advocacy efforts. In addition to advocacy initiatives led by counselors, counselors can support their clients who have experienced IPV victimization to engage in self-advocacy, as well as advocacy efforts designed to promote positive social change. This study examines how survivors of IPV (n=123) think about themselves as potential or actual advocates, as well as survivors’ considerations for engaging in advocacy efforts. We apply content analysis methodology to identify themes within respondents’ qualitative responses to an advocacy-related question on an electronic survey on the process of overcoming abuse. The following themes emerged: the significance of survivors’ involvement in advocacy, survivors’ personal qualities and skills required for effective advocacy, validation of survivors’ right to choose whether or not to engage in advocacy, and examples of survivors’ large and small-scale advocacy efforts. The ACA Advocacy Competencies are then used to organize and operationalize survivors’ perceptions and experiences related to their involvement in advocacy efforts. The unique opportunities and challenges that survivors may encounter when they engage in advocacy initiatives at the individual, community, and societal levels are considered. This study aims to expand the concept of self-advocacy to survivors of IPV and other similarly marginalized groups, highlighting the potential for personal empowerment and social change.